Efforts to restore the Sanctity of the Constitution in Islamic Republic of Pakistan: A Study in Context of General Musharraf’s Emergency on 3rd November 2007 (Al-Qamar, 2019)
This article walks around the fight back to ignite the constitutional judicial power by the apex court of Pakistan and imposition of emergency to snub, dictate, and introduce loyal judges to guard political and extra-constitutional personal interests. The meeting points of this article based on two questions: first, what made the supreme court to go against the then-existing military dictator; second, what was ‘irritating’ and authority challenging decision in public litigation, constitutional and administrative domain; third, how did Musharraf tackle, de-seat, and house arrest the judges, and brought the PCO judges, and de facto supreme court by way of imposing emergency. It is also made clear how de facto Supreme Court accommodated and paid back Musharraf by letting him take over the office of President of Pakistan, legalizing all the illegal actions and orders made by Musharraf, and reversed all the orders made by the previous Supreme Court judges. During all this time, lawyers were very active for the sanctity of the Constitution, law, and democracy, so they, with the cooperation of civil society and political parties, did a great dent to Musharraf and all his efforts to remain in power failed and he had to resign to avoid impeachment.
Keywords: Constitution; Emergency; Supreme Court; Musharraf